Nasal Breathing Assessment Using Computational Fluid Dynamics: An Update from the Rhinologic Perspective - Hildebrandt, Thomas; Heppt, Werner Johannes (Facial Plastic Surgery, 2024)
An objective assessment of nasal breathing is currently insufficiently achievable. The application of computational fluid dynamics for this purpose is increasingly gaining attention. However, the suggested specific frameworks can differ considerably. To the best of our knowledge, there is not yet a widely accepted clinical usage of computational fluid dynamics. In this article, selected aspects are addressed that might be crucial for future development and possible implementation of computational fluid dynamics in rhinology.
Keywords: computational fluid dynamics; statistical shape model; nasal breathing; flow field; wall shear stress; intranasal airflow